IMPACT OF AN EMS–FAMILY MEDICINE–LABORATORY–PHYSIOTHERAPY COLLABORATIVE MODEL ON ACUTE MUSCULOSKELETAL INJURY ASSESSMENT AND OUTCOMES - AHMED BIN MOHAMMED BIN QAHAT ALDIGHRIR, MABKHOOT MUBARAK ALHAGBANI, MISLAT MOHAMMED ALSAHALI, RAWAN FAHAD OTHMAN ALHAMYANI, ABDULLAH NASHI ABDULLAH ALOTAIBY, MAHA AHMAD HASSAN ALZAHRANI; AMAL AWADH AL-TALHI, MAJED MOHAMMED MUBARAK ALQAHTANI, WAFA MUNIF ALHARBI, ABDULHADI HAMAD ALQAHTANI, ABDULLAH BURKI ALMUTAIRI, MUBARAK ABDULLAH ALHAGBANI (TPM – Testing, Psychometrics, Methodology in Applied Psychology, 2025)
Acute musculoskeletal injuries impose a substantial and often inefficient burden on emergency and primary care services, frequently resulting in unnecessary resource utilization and delayed access to definitive rehabilitation. Conventional fragmented care pathways, typically involving emergency department presentation followed by delayed and siloed referrals, contribute to suboptimal functional recovery and increased long-term healthcare costs. Addressing these inefficiencies requires an integrated care pathway that coordinates assessment and management from initial triage through to definitive treatment. This paper proposes and establishes a conceptual framework for a novel collaborative model integrating Emergency Medical Services, Family Medicine or General Practice, Laboratory services, and Physiotherapy. The primary objective is to synthesize best-practice evidence to define a feasible, coordinated pathway hypothesized to improve the efficiency of acute musculoskeletal injury assessment and optimize patient outcomes, thereby providing a robust blueprint for future clinical evaluation. A conceptual framework methodology was employed, using a structured and focused synthesis of evidence from academic databases, including MEDLINE and the Cochrane Library, alongside relevant health policy reports. The synthesis targeted evidence supporting the safety and efficiency of four core components: prehospital triage by Emergency Medical Services to enable emergency department avoidance for eligible patients; direct musculoskeletal assessment by Family Medicine or General Practice to provide rapid medical evaluation; the selective use of targeted laboratory diagnostics to safely exclude systemic or inflammatory red flags; and expedited access to physiotherapy to reduce symptom chronicity and functional decline. This evidence informed the construction of a step-by-step patient pathway, defining key decision points, communication processes, and proposed performance metrics. The resulting framework describes a coordinated pathway in which Emergency Medical Services direct eligible patients to a fast-track Family Medicine or General Practice appointment. Standardized clinical screening is used to guide management, with laboratory testing applied only when clinically indicated, enabling prompt referral to physiotherapy. The model is conceptually designed to reduce the primary performance indicator, time to definitive care. Secondary anticipated outcomes include reductions in unnecessary diagnostic imaging, lower emergency department re-presentation rates, and improved patient-reported functional outcomes at twelve weeks post-injury compared with standard care. The proposed Emergency Medical Services, Family Medicine or General Practice, Laboratory, and Physiotherapy collaborative model offers a comprehensive, evidence-based response to the fragmented management of acute musculoskeletal injuries. This conceptual framework provides a clear protocol structure and justification to support future implementation and rigorous clinical evaluation of an integrated care delivery system.